Bulgarian Transition and the Way of Destabilization of Constitutionalism - Todorova, Elka; Popov, Miroslav (Research Papers, 2015)
Bulgarian state is in crisis, the main reason for that is the lack of analysis of the actual state of constitutionalism and anti-constitutionalism. Over the past quarter century, a number of state institutions did not meet fully their constitutional obligations towards the citizens and the state as a whole: a) the state abdicated from the defense of a number of constitutionally enshrined rights of citizens; b) a condescending attitude has been imposed to the new constitution, while its fundamental principles are interpreted and developed in the current legislation in a way different from the actual meaning of the constitutional norms; c) fundamental to the modern parliamentary practices issues are problematized; d) main elements of the democratic society are disclaimed.Instead of providing examination and analytical assessment of the Bulgarian judiciary law enforcement nihilism takes place. The war against the Bulgarian statehood has many motives, the main being economic interests and incompetence.
Keywords: Constitution; Constitutionalism; Anti-constitutionalism; Parliamentarism; Judicial norms; Judicial practices; Judiciary